Hubungan Dukungan Suami dengan Pemberian Asi Eksklusif di Wilayah Kerja Puskesmas Kiajaran Wetan - Eleni Kenanga Purbasary (Poltekkes Kemenkes Mataram, 2022)
ABSTRACTThe achievement of exclusive breastfeeding is still low, one of the reasons is the husband's lack of support for the mother. The husband's motivation in supporting breastfeeding is very much needed by the mother so that exclusive breastfeeding runs smoothly. Mother's Milk (ASI) is the perfect food that babies need in the first six months of life. The purpose of this study was to determine the relationship between husband's support and exclusive breastfeeding in the Work Area of the Kijajar Wetan Health Center. The research method used is descriptive analytic with a cross sectional approach. The population in this study were mothers who had babies 0-6 months. Data collection techniques using proportionate stratified random sampling with a total of 138 respondents and using a questionnaire. The results of this study found that as many as 71 (51.4%) mothers gave exclusive breastfeeding and as many as 77 (55.8%) received good husband support and statistical test P value 0.000 which means there is a relationship between husband's support and exclusive breastfeeding. Suggestions for husbands always provide motivation and accompany their wives in exclusive breastfeeding because the husband's role is needed by mothers in increasing exclusive breastfeeding